AMBAS: an autonomous multimodal biometric authentication system. (5th July 2019) - Mansour, Abdeljebar; Sadik, Mohamed; Sabir, Essaid; Jebbar, Mostafa
The traditional authentication techniques based on single factors such as passwords and tokens suffer from problems related to their robustness. Moreover, multi-factor authentication based on multimodal biometrics (MFA-MB) technique is used to overcome the drawbacks related to these techniques and also the problems related to the biometrics using single traits. Based on MFA-MB, this paper aims to model and develop an autonomous multimodal biometric authentication system called 'AMBAS' using discrete-time Markov chains in order to decrease the complexity of the multimodal biometric system used in the MFA-MB scheme. In fact, giving the self-control to the AMBAS will improve therefore one user experience and achieve as well good performances in terms of authentication time. This system aims to identify users according to four different methodologies. While giving a case study with three-modal biometrics, we exhibit the performed algorithms. A simulation is done in order to test the system performances and usefulness.